Laying the cornerstone for Virginia Union University Library
Was formerly the Belgian Pavilion at New York World's Fair. Men in photo from left to right: Rev. Theodore Adams, D.D., Chairman of Virginia Union University Board Dr. J.M. Ellison, President elect of the university Dr. Jan A. Gois, Deputy Commissioner for Belgium New York World's Fair Dr. Hupo van Kuyck, supervising architect Dr. William J. Clark, retiring president of university. Leighton No. 310.